Finite element stress and vibration analysis of corrugated sheets - Lim, Jia Hau (Nanyang Technological University, 2024)
Corrugated sheets, characterised by their wave-like shape, are widely used in industries due to their high stiffness-to-weight ratio compared to flat sheets. In this project, finite element analysis is carried out to study the load carrying capacity, stiffness characteristics, natural frequency, and mode shapes of corrugated sheets. Varying number of waves have been considered with different wave shapes (sinusoidal, rectangular, square, and triangular). Exploration of how corrugated sheets react under critical buckling load will also be done with sinusoidal waves. Firstly, the models will be created in ANSYS Parametric Design Language (APDL). Secondly, the model will be meshed to generate a finite element model. Thirdly, boundary conditions and loads will be applied before solving the model with finite element analysis. The results show that for the same volume of sheet metal used, corrugated sheets exhibit higher load carrying capacity, stiffness, natural frequency, and critical buckling load compared to flat sheets. Load carrying capacity, stiffness and natural frequency for corrugated sheets tend to decrease as the number of waves increases. The analyses are carried out with and without warping constraints at the loaded edge. Results show that corrugated sheets with warping constraints exhibit higher load carrying capacity, stiffness, natural frequencies, and critical buckling load. Among all the wave shapes, sinusoidal corrugated sheets have the highest load carrying capacity while rectangular corrugated sheets have the highest natural frequency.